SISHANKAMRATA: An Approach to a Versatile Asymmetric Strategy for Weak and Strong from Clausewitz Trinity Perspective - Maulidiyawan, Robby; Susanto, Rudy; Suhirwan (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This study aims to examine the relevance of this system at a time when asymmetric war elements dominate many current conflicts. This research has two problem formulations, the research objectives of which are as follows: (1) How does SISHANKAMRATA integrate the principles of Clausewitz's Trinity to create a cohesive and adaptive defence strategy against modern asymmetric threats? (2) What are the strengths and limitations of SISHANKAMRATA as a strategic model for weak and strong actors? The method used is a qualitative research method of library research with the acquisition of secondary data such as laws, doctrine, posture, books and scientific articles. This study concludes that SIHANKAMRATA is versatile for facing conventional, asymmetric, and even hybrid threats. The nature of SISHANKAMRATA also invites people to prioritize this system through quantity. However, the weakness lies in the quality, in terms of the preparation stage, and in the later stage of maintaining it. It is crucial during the conflict since Indonesia possesses vast territory and archipelago.